Development of Interactive Learning Media in Computer Subjects and Basic Networks in Vocational High Schools - Islapirna Islapirna; Fadhilah; Yeka Hendriyani; Wakhinuddin (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
The use of technology in the educational process is one of the aspects that influence or help fulfill a quality learning process in an effort to achieve educational goals. If the use of this technology is not carried out, there will be many difficulties encountered in the learning process which are given directly by the teacher. This will affect many aspects, such as the teacher's explanation which is difficult to accept and understand and the lack of concentration of students during the learning process because the media provided is monotonous. This study aims to develop learning media and produce valid, practical, and effective media in the subject of Basic Computers and Networks for class X Computer Engineering and Basic Networks at YAPIM Vocational School. The method used in this study is the Research and Development (R&D) method, with a four-D development model. The results obtained from this study are web-based interactive learning media. Based on the results of the study it was concluded that the developed media was declared valid on the media aspect of 86%, the material aspect with a yield of 96%. The developed media is practical with the practicality value of the teacher's response with a result of 97.92% and the student's response is 88.29%, and the resulting web-based interactive learning media is effectively used with the posttest results seen from the students' classical completeness of 100% and the gain score of 0.50 in the moderate category.